The Study of Max-Min Composition in Fuzzy Relation - Shah, Yogendra Prasad (Patan Prospective Journal, 2023)
One of the foundational concepts in both pure and applied mathematics is the notion of relations. Fuzzy relations extend this concept much like fuzzy sets generalize the fundamental idea of sets. This study provides a comprehensive overview of operations, compositions, and the various types inherent in fuzzy relations.